The convenient determination of palladium at a solid electrode via adsorptive stripping voltammetry at a glassy carbon electrode modified with a random array of mercury nanodroplets - Abiman, P.; Wildgoos, G.G.; Xiao, L.; Compton, R.G. (Wiley-VCH Verlag GmbH & Co. KGaA, 2008)
The detection of palladium using adsorptive stripping voltammetry reported by Wang et al. (J. Wang, K. Varughese Anal. Chim. Acta 1987, 199, 185 [3]) at a hanging mercury drop electrode is extended to a more convenient solid electrode. To this end a random array of 3.5 × 10 8 mercury nanodroplets per cm 2 (65 nm average diameter) was electrodeposited on a glassy carbon substrate. Adsorptive stripping voltammetry was performed using 2 × 10 -4 M dimethylglyoxime as a chelating agent for the Pd(II) ion, with accumulation at -0.20 V vs. SCE for 120 s and a linear detection range of 5 - 150 μM was determined with a limit of detection of 1.6 μM.
Keywords: Adsorptive stripping voltammetry; Dimethylglyoxime; Glassy carbon; Mercury; Nanoelectrode array; Palladium